2001
DOI: 10.1007/s002210100844
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between saccadic eye movements and cortical activity as measured by fMRI: quantitative and qualitative aspects

Abstract: We investigated the quantitative relationship between saccadic activity (as reflected in frequency of occurrence and amplitude of saccades) and blood oxygenation level dependent (BOLD) changes in the cerebral cortex using functional magnetic resonance imaging (fMRI). Furthermore, we investigated quantitative changes in cortical activity associated with qualitative changes in the saccade task for comparable levels of saccadic activity. All experiments required the simultaneous acquisition of eye movement and fM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
2
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 63 publications
12
87
2
8
Order By: Relevance
“…Functional MRI was conducted with a 3-Tesla Siemens scanner (Allegra) using a whole-brain, echo-planer T2*-weighted imaging sequence. We identified regions of interest (ROIs) via separate functional localizer scans on each participant for early visual cortex with retinotopic mapping, 10 lateral occipital cortex 11 , intraparietal sulcus (IPS) 12 and the frontal/supplementary eye fields 13 . Image data were co-registered to high-resolution T1-weighted structural scans and analysis performed on the cortical surface with FreeSurfer 8,9 .…”
Section: Methodsmentioning
confidence: 99%
“…Functional MRI was conducted with a 3-Tesla Siemens scanner (Allegra) using a whole-brain, echo-planer T2*-weighted imaging sequence. We identified regions of interest (ROIs) via separate functional localizer scans on each participant for early visual cortex with retinotopic mapping, 10 lateral occipital cortex 11 , intraparietal sulcus (IPS) 12 and the frontal/supplementary eye fields 13 . Image data were co-registered to high-resolution T1-weighted structural scans and analysis performed on the cortical surface with FreeSurfer 8,9 .…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested in a study looking at functional interactions between pro-and antisaccades that the presupplementary motor area (pre-SMA) coordinates with the FEF to maintain a controlled, preparatory set for task appropriate oculomotor execution . Saccade frequency and amplitude was varied (Kimmig et al, 2001) and high correlation between frequency and BOLD signal was found along with higher BOLD activation in antisaccades over prosaccades. Merriam et al (2001) found that comparison of visually guided saccades with fixation revealed activation in all three cortical eye fields: SEF, FEF, and PEF.…”
Section: Fmri and Oculomotor Functionmentioning
confidence: 95%
“…As a result of the increase in general fMRI studies, there has also been an increase of studies investigating many aspects of the vision science. These studies include normal eye movements such as optokinetic nystagmus (OKN) (Bense et al, 2006a;Bucher et al, 1997;Dieterich et al, 1998;2003;Kashou et al, 2006;Kashou, 2008;Kashou et al, 2010;Konen et al, 2005;Petit & Haxby, 1999;Schraa-Tam et al, 2008), saccades (Berman et al, 1999;Bodis-Wollner et al, 1997;Connolly et al, 2005;Cornelissen et al, 2002;Darby et al, 1996;Ettinger et al, 2008;Haller et al, 2008;Hayakawa et al, 2002;Kimmig et al, 2001;Konen et al, 2004;Luna et al, 1998;Merriam et al, 2001;Miller et al, 2005;Mort et al, 2003;Müri et al, 1996;Petit et al, 1997;Rosano et al, 2002), smooth pursuit (Barton et al, 1996;Berman et al, 1999;Freitag et al, 1998;Ohlendorf et al, 2010;Petit et al, 1997;Petit & Haxby, 1999;Rosano et al, 2002;Tanabe et al, 2002), and gaze (Andersson et al, 2007;Deutschländer et al, 2005). There have also been studies that look at varying aspects of visual perception such as: effect of age …”
Section: Fmri Vision Science Studiesmentioning
confidence: 99%
“…First, we performed a behavioral pre-fMRI experiment (Exp 4) similar to Exp 1 but with presentation duration of 250ms (frame-cue and picture presented simultaneously). Exp 4 simply ensured that robust memory enhancement for Go vs. NoGo stimuli is observed at this shorter presentation time, employed so as to minimize saccades, which not only lead to spurious BOLD effects (Kimmig et al, 2001) but also represent another type of action that increases LC activity in non-human primates (Kalwani et al, 2014). The results of Exp 4 once more replicated the main finding from Exp 1-3 (better memory for Go vs. NoGo items ( 21 = 2.26; p = 0.03; Figure 15A).…”
Section: Action-induced Episodic Memory Enhancement Is Associated Witmentioning
confidence: 99%